2015
DOI: 10.1021/acs.inorgchem.5b01983
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Coordination Polymers Self-Assembled from Aminoalcohols and Pyromellitic Acid: Highly Active Precatalysts for the Mild Water-Promoted Oxidation of Alkanes

Abstract: Three novel water-soluble 2D copper(II) coordination polymers-[{Cu2(μ2-dmea)2(H2O)}2(μ4-pma)]n·4nH2O (1), [{Cu2(μ2-Hedea)2}2(μ4-pma)]n·4nH2O (2), and [{Cu(bea)(Hbea)}4(μ4-pma)]n·2nH2O (3)-were generated by an aqueous medium self-assembly method from copper(II) nitrate, pyromellitic acid (H4pma), and different aminoalcohols [N,N-dimethylethanolamine (Hdmea), N-ethyldiethanolamine (H2edea), and N-benzylethanolamine (Hbea)]. Compounds 2 and 3 represent the first coordination polymers derived from H2edea and Hbea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 57 publications
3
40
0
Order By: Relevance
“…Polynuclear metal complexes containing voluminous organic [63,66,118,119,[129][130][131]186,[213][214][215][216][217][218][234][235][236][237][238][239][240][241] or siloxane [221][222][223][224][225][226][227][228] ligands are also very efficient in oxidations of organic compounds including saturated hydrocarbons with peroxides. For example, dinuclear copper complex 11 [221,224] and hexairon complex 15 (for the structure, see Figure 9) affording the products of cyclohexane oxidation in a very high yield of 46% (see Figure 10 [226]) can be considered as "inorganic models of methane monooxygenases."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polynuclear metal complexes containing voluminous organic [63,66,118,119,[129][130][131]186,[213][214][215][216][217][218][234][235][236][237][238][239][240][241] or siloxane [221][222][223][224][225][226][227][228] ligands are also very efficient in oxidations of organic compounds including saturated hydrocarbons with peroxides. For example, dinuclear copper complex 11 [221,224] and hexairon complex 15 (for the structure, see Figure 9) affording the products of cyclohexane oxidation in a very high yield of 46% (see Figure 10 [226]) can be considered as "inorganic models of methane monooxygenases."…”
Section: Discussionmentioning
confidence: 99%
“…Pombeiro, Martins, Guedes da Silva [234][235][236][237][238], Kirillov [234,235,[239][240][241], and other scientists [242] synthesized various polynuclear complexes, coordination polymers, and derived metal integrated mesoporous matrices and demonstrated high catalytic activity of these materials in oxidations with peroxides. Figures 13-15 show the examples of such catalysts.…”
Section: Polynuclear Metal Complexes As Catalystsmentioning
confidence: 99%
“…However, more efforts to systematically study the potential properties of lesser-dimensional CPs have been made recently [44][45][46][47][48][49][50] . Despite their structural simplicity compared to MOFs, one dimensional (1D) CPs in particular are generally easier to synthesize and the resulting framework can be tuned more effectively in order to generate structures with maximized application potential 51,52 .…”
Section: Recent Advances Of One-dimensional Coordination Polymers As mentioning
confidence: 99%
“…Moreover, the influence of additional water in the reaction mixture (Table 2, Entries 5-7) has been studied, since some authors recently reported its promoting effect on the reaction rate in cyclohexane oxidation. [51] However, no beneficial effect of water addition has been observed in the oxidation of -pinene under optimized conditions. Moreover, the addition of a co-solvent, which could improve the solubility of the terpenic olefin, did not improve the results (Table 2, Entry 8).…”
Section: -Scheme 4 -mentioning
confidence: 99%